An annotated bibliography of American Indian and Eskimo autobiographies - Brumble, H. David (University of Nebraska Press, 1981)
Cites printed versions of first-person narratives by North American Indians and Eskimos, including Canadian material.
Includes indexes.
Keywords: Indians of North America -- Biography -- Bibliography.; Eskimos -- Biography -- Bibliography.; Peuples autochtones -- Amérique du Nord -- Biographies -- Bibliographie.; Inuits -- Biographies -- Bibliographie.; REFERENCE.; Indians of North America; Indianen.; Eskimo's.; Bibliographies; Herinneringen (vorm); Bibliografieën (vorm)